Development of a visualization model for detecting fractures in Kuala Lumpur limestone for geological engineering purposes - Mohamed Elmahdy, Samy Ismail Mohamed (2012)
The major geotechnical engineering problems confronted constructions and structure designs on Kuala Lumpur Limestone bedrock in Kuala Lumpur are: cavities, sinkholes, pinnacles, excavation collapses and irregular surface of limestone bedrock. To address these problems, a set of techniques were developed for (1) automatically detecting regional geological structures, (2) detecting geological structure intersections (dissolution zones) and their associated extreme karst features, and (3) visualizing geological structures and their associated karst features. These techniques include geological prediction model, hydro-morphological model and moropho-visualization model. These techniques were applied to Kuala Lumpur Limestone bedrock in Malaysia, by focusing on the adjacent mountainous areas and the geometries of ex-opencast mining ponds, depressions, major rivers and soil moisture. These features were spatially correlated and clarified by rose diagrams and semivariogram models.Visualizations technique was developed by applying percentile stretching and Soble filter with 10% threshold and equalization enhancement to the calculated thematic maps. Several new geological fractures (faults, joints and bedding plains) were detected, mapped and visualized for the first time using the modified methods. Their orientations are dominantly found in NE-SW, NW-SE, WNW-ESE and E-W directions and correspond well with regional tectonic zones of the South East Asia. The study revealed that the ridge which reflect footwall of fault zone and valley which reflect fault plain represent 47% and 41% respectively.